22.5k views
2 votes
5(2x+6)=-4(-5 – 2x) + 3x​

User Rahmat
by
5.1k points

2 Answers

0 votes

Answer:


x=10

Explanation:


5(2x+6)=-4(-5 -2x) + 3x


\longrightarrow Use the distributive property to multiply 5 by 2x+6, and -4 by -5 - 2x.


10x+30=20+8x+3x


\longrightarrow Combin 5x and 2x to get 11x:-


10x+30=20+11x


\longrightarrow Subtract 11x from both sides:-


10x+30-11x=20


\longrightarrow Combine 10x and -11x to get -x:-


-x+30=20


\longrightarrow Subtract 30 from both sides:-


x=20-30


\longrightarrow Subtract 30 from 20 to get -10:-


-x=-10


\longrightarrow Multiply both sides by -1:-


x=10

OAmalOHopeO

User Cornel Verster
by
4.8k points
1 vote

Answer:

x = 10

Explanation:

10x+30 = 20+8x+3x

30 = 20+x

x = 10

User Oscar Velandia
by
4.4k points